2009
DOI: 10.1002/mus.21324
|View full text |Cite
|
Sign up to set email alerts
|

Atypical deep peroneal neuropathy in the setting of an accessory deep peroneal nerve

Abstract: We report a case of deep peroneal neuropathy resulting in foot drop with preserved toe extension. These unexpected findings were the result of the presence of an accessory deep peroneal nerve that provided total innervation of the extensor digitorum brevis. We review the literature on total innervation of the extensor digitorum brevis by the accessory deep peroneal nerve with and without an associated deep peroneal nerve lesion. Muscle Nerve 40: 313-315, 2009.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 9 publications
0
5
1
Order By: Relevance
“…In our study there is no difference between female and male in distribution of APN. Other issue that was detected and explained in our study is detection of EDB agenesis that was not shown and mentioned in other studies [2,12].…”
Section: Resultscontrasting
confidence: 47%
See 3 more Smart Citations
“…In our study there is no difference between female and male in distribution of APN. Other issue that was detected and explained in our study is detection of EDB agenesis that was not shown and mentioned in other studies [2,12].…”
Section: Resultscontrasting
confidence: 47%
“…This difference could be due to some genetic issues and/or techniques used that needs further studies to be confirmed. Also Kayal and et al described this difference" the reported evidence is higher in studies that routinely applied stimulation behind the lateral malleolus during the performance of peroneal motor conduction studies" [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The lateral terminal branch supplies the extensor digitorum brevis muscle, and it provides interosseous branches that innervate the tarsal and metatarsophalangeal joints of the middle three toes. 12 The proximal segment of the DPN is equally well seen on US and MRN, whereas the distal branches are difficult to identify unless they are abnormal. We favor MRN for DPN evaluation because it better shows the nerve signal intensity changes as well as the related muscle denervation changes.…”
Section: Deep Peroneal Nervementioning
confidence: 99%